2015
DOI: 10.1073/pnas.1507142112
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution of malaria parasites in French Guiana: Reversal of chloroquine resistance by acquisition of a mutation in pfcrt

Abstract: In regions with high malaria endemicity, the withdrawal of chloroquine (CQ) as first-line treatment of Plasmodium falciparum infections has typically led to the restoration of CQ susceptibility through the reexpansion of the wild-type (WT) allele K76 of the chloroquine resistance transporter gene (pfcrt) at the expense of less fit mutant alleles carrying the CQ resistance (CQR) marker K76T. In low-transmission settings, such as South America, drug resistance mutations can attain 100% prevalence, thereby preclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
136
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 44 publications
11
136
0
Order By: Relevance
“…Polymorphisms in addition to those commonly described in African isolates have been identified in other regions, in some cases with biochemical and clinical consequences (49,50). Sequencing of pfcrt in a subset of samples either under or not under the selective pressure of DP identified a few previously unidentified pfcrt mutations, but it did not suggest that additional polymorphisms were selected by DP.…”
Section: Discussionmentioning
confidence: 88%
“…Polymorphisms in addition to those commonly described in African isolates have been identified in other regions, in some cases with biochemical and clinical consequences (49,50). Sequencing of pfcrt in a subset of samples either under or not under the selective pressure of DP identified a few previously unidentified pfcrt mutations, but it did not suggest that additional polymorphisms were selected by DP.…”
Section: Discussionmentioning
confidence: 88%
“…However, the potential role of background mutations and their association with artemisinin resistance needs further validation in South America. Additionally, most of the Suriname samples (62%) had the PfCRT C350R mutation, which has been associated with a CQ phenotypic reversion and a strong piperaquine drug-selective pressure (5). Given that gold miners living in the forest are known to self-medicate with dihydroartemisinin-piperaquine-trimethoprim tablets, it is not surprising that this PfCRT mutation is found in high frequency in these study samples, especially if we consider that 87% of the patients came from artisanal gold mining areas in French Guiana.…”
Section: Figmentioning
confidence: 99%
“…82,90 For instance, isolates containing parasites with a variant of the Dd2 Pfcrt allele carrying either 97Y, 343L, or 353V have higher median PSA survival rates than those harboring the Dd2 allele. 82 In French Guiana, Pelleau and others also found that the acquisition of the C350R substitution in the Pfcrt gene decreased susceptibility to PPQ, suggesting that PPQ pressure drove the expansion of this allele.…”
Section: Resistance To Ppq: Research Challengesmentioning
confidence: 99%
“…82 In French Guiana, Pelleau and others also found that the acquisition of the C350R substitution in the Pfcrt gene decreased susceptibility to PPQ, suggesting that PPQ pressure drove the expansion of this allele. 90 As the 353V mutation (frequently observed in Cambodia) is located close to 350R, further investigations, such as genome editing, should be carried out to assess the role of Pfcrt mutations in the genetic background of Cambodian parasites.…”
Section: Resistance To Ppq: Research Challengesmentioning
confidence: 99%